A morphological study of the vine snout beetle, Cryptopharynx vitis Marshall (Coleoptera: Curculionoidea) - Van den Berg, H. C (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1967.